기술효율, 환경효율, 규모효율과 그 결정요인 분석 - 한국농가의 소득계층을 중심으로 - 강상목; Sang Mok Kang; 김태수; Tae Soo Kim; 김태구; Tae Gu Kim; 이동명; Dong Myong Lee (자원·환경경제연구, 2005)
The purpose of this paper is to estimate technical efficiency, scale efficiency, and environmental efficiency by income level of Korean farms, and analyze the factors to decide three efficiencies. Depending on the non-parametric methods, we estimate technical using inputs and outputs of total farms without assuming of goods or behavior of optimization. The average technical efficiency of total firms under constant return to scale and strong disposability is 0.437. The technical inefficiency was caused by 47.7% in pure technical inefficiency, 11.3% in scale failure, and 3.2% in environmental inefficiency. The number of firms under increasing return to scale occupied almost 70% and 27% of total firms respectively. Higher are income class, middle debt & long debt per asset, and N effluents per cultural land, higher technical efficiency. The increases of BOD discharges per cultural land and machines per cultural land deteriorate environmental efficiency. 본 연구의 목적은 투입물 효율함수를 이용하여 한국농가의 소득계층을 대상으로 기술효율, 환경효율, 규모효율을 측정하고, Tobit 모형으로 그 결정요인을 분석하는 것이다. 본 연구는 비모수적(nonparametric) 방법에 의존하여 재화의 가격이나 최적화 행동에 관한 가정없이 투입요소와 산출량에 의존하여 기술효율을 계측한다. 생산기술은 바람직한 재화와 바람직하지 못한 오염물의 결합생산을 모형화한다. 규모불변과 강처분 하에서 평균 기술효율 수준은 0.437 이었다. 기술비효율의 원인은 순수기술비효율이 47.7%, 규모비효율은 11.3%, 환경비효율 3.2%의 순이다. 규모체증 상태에서 생산농가는 전체농가의 70%를 점유하고 규모체감 상태에서 생산농기는 전체농가의 27%에 이른다. 효율성을 결정하는 요인으로 소득계층이 높을수록 중장기 부채가 높을수록 단위면적당 질소배출량이 높을수록 기술효율은 높았고, 경지면적당 농업경영비가 높을수록 기술효율은 저하되었다. 환경효율에서는 BOD 배출량, 단위면적당 기계도입, 자본의 생산성 유의적이고 음(-)으로 나타나, 청정기술이 아닌 단순한 기계화의 확대는 환경효율을 악화시키는데 영향을 주고 있음을 시사한다.